Regulation of pyroptosis in cardiovascular pathologies: Role of noncoding RNAs - Jinning Gao; Xiatian Chen; Pengcheng Wei; Yin Wang; Peifeng Li; Kai Shao (Elsevier, 2021)
Cardiovascular disease (CVD) is one of the most important diseases endangering human life. The pathogenesis of CVDs is complex. Pyroptosis, which differs from traditional apoptosis and necrosis, is characterized by cell swelling until membrane rupture, resulting in the release of cell contents and activation of a strong inflammatory response. Recent studies have revealed that inflammation and pyroptosis play important roles in the progression of CVDs. Noncoding RNAs (ncRNAs) are considered promising biomarkers and potential therapeutic targets for the diagnosis and treatment of various diseases, including CVDs. Growing evidence has revealed that ncRNAs can mediate the transcriptional or posttranscriptional regulation of pyroptosis-related genes by participating in the pyroptosis regulatory network. The role and molecular mechanism of pyroptosis-regulating ncRNAs in cardiovascular pathologies are attracting increasing attention. Here, we summarize research progress on pyroptosis and the role of ncRNAs, particularly microRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs), in the regulation of pyroptosis in CVD pathologies. Identifying these disease-related ncRNAs is important for understanding the pathogenesis of CVDs and providing new targets and ideas for their prevention and treatment.